2022
DOI: 10.1044/2021_jslhr-21-00454
|View full text |Cite
|
Sign up to set email alerts
|

Vocabulary Growth in Mandarin-Speaking Children With Bilateral Cochlear Implants, Bimodal Stimulation, or Unilateral Cochlear Implants During the First Year After Activation

Abstract: Purpose: The purpose of this study was to evaluate vocabulary development in Mandarin-speaking children with bilateral cochlear implants (CIs), bimodal stimulation (CI plus hearing aids [HAs]), or unilateral CIs during the first year after CI activation. Method: Participants included 23 children with simultaneous bilateral CIs, 23 children with bimodal stimulation, and 15 children with unilateral CIs. They all received CIs before 30 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Xu et al . 18 showed that the vocabulary growth rate in the cochlear implant and cochlear implant group was better than that in the cochlear implant and hearing aid group. Sharma et al .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Xu et al . 18 showed that the vocabulary growth rate in the cochlear implant and cochlear implant group was better than that in the cochlear implant and hearing aid group. Sharma et al .…”
Section: Discussionmentioning
confidence: 91%
“…Guerzoni et al 17 found that unilateral cochlear implant group children were inferior in reading comprehension to cochlear implant and cochlear implant, and cochlear implant and hearing aid groups. Xu et al 18 showed that the vocabulary growth rate in the cochlear implant and cochlear implant group was better than that in the cochlear implant and hearing aid group. Sharma et al 19 pointed out that the cochlear implant and cochlear implant group had stronger speech noise perception and sound source localisation ability than the cochlear implant group.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Long et al ( 10 ) found that the auditory preverbal skills of the BICI group were better than those of their unilateral CI peers during the 24 months of CI use. Another longitudinal study ( 11 ) explored the development of vocabulary in the children speaking native Mandarin after CIs and the faster growth of the receptive vocabulary was observed in the children with simultaneous BICIs compared to those with UCIs. In these studies, the limited sample sizes and inappropriate statistical analysis methods led to less rigorous research results.…”
Section: Introductionmentioning
confidence: 99%